The impact of supply chain operational capability on business performance: Empirical finding from small and medium enterprises in Yogyakarta - Danu Oki Prastia; Siti Nursyamsiah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2016)
This study aimed to analyze the effect of supply chain capability on business performance of small and medium enterprises (SMEs) in Yogyakarta. Supply chain capability is the ability to coordinate activities related to the flow of materials and products, both of which are within the organization and between organizations. Supply chain operational capability is measured using 3 capabilities including structural, logistical and the technological capability. The sample of this study were selected using simple random method. A total of 193,391 SMEs were analysed this study and resulting 100 SMEs that were used as the subjects. Moreover, this study employed multiple regression analysis to analyse the proposed hypothesis. The results showed that simultaneously and partially operational capability of supply chain consisting of the structural, logistics and the technological capability affect the business performance of SMEs in Yogyakarta.